The association between childhood fractures and adolescence bone outcomes: a population-based study, the Tromsø Study, Fit Futures - Christoffersen, Tore; Emaus, Nina; Dennison, Elaine; Furberg, Anne-Sofie; Gracia-Marco, Luis; Grimnes, Guri; Nilsen, Ole-Andreas; Vlachopoulos, Dimitris; Winther, Anne; Ahmed, Luai A. (Osteoporosis International, 2017)
This is a post-peer-review, pre-copyedit version of an article published in Osteoporosis International . The final authenticated version is available online at: https://doi.org/10.1007/s00198-017-4300-0 . SUMMARY : Childhood fracture may predict persistent skeletal fragility, but it may also reflect high physical activity which is beneficial to bone development. We observe a difference in the relationship between previous fracture and bone outcome across physical activity level and sex. Further elaboration on this variation is needed. PURPOSE : Childhood fracture may be an early marker of skeletal fragility, or increased levels of physical activity (PA), which are beneficial for bone mineral accrual. This study investigated the association between a previous history of childhood fracture and adolescent bone mineral outcomes by various PA levels. METHODS : We recruited 469 girls and 492 boys aged 15-18 years to this study. We assessed PA levels by questionnaire and measured areal bone mineral density (aBMD) and bone mineral content (BMC) using dual-energy X-ray absorptiometry (DXA) at arm, femoral neck (FN), total hip (TH), and total body (TB) and calculated bone mineral apparent density (BMAD, g/cm3). Fractures from birth to time of DXA measurements were retrospectively recorded. We analyzed differences among participants with and without fractures using independent sample t test. Multiple linear regression was used to examine the association between fractures and aBMD and BMC measurements according to adolescent PA. RESULTS : Girls with and without a previous history of fracture had similar BMC, aBMD, and BMAD at all sites. In multiple regression analyses stratified by physical activity intensity (PAi), there was a significant negative association between fracture and aBMD-TH and BMC-FN yet only in girls reporting low PAi. There was a significant negative association between forearm fractures, BMAD-FN, and BMAD-arm among vigorously active boys. CONCLUSION : Our findings indicate a negative association between ...